Effects of increased intensity of intermittent training in runners with differing VO2 kinetics - Millet, G. P.; Libicz, S.; Borrani, F.; Fattori, P.; Bignet, F.; Candau, R. (European Journal of Applied Physiology, 2003)
The purpose of this study was to test the hypothesis that athletes having a slower oxygen uptake (VO2) kinetics would benefit more, in terms of time spent near VO2max, from an increase in the intensity of an intermittent running training (IT). After determination of VO2max, vVO2max (i.e. the minimal velocity associated with VO2max in an incremental test) and the time to exhaustion sustained at vVO2max (T lim), seven well-trained triathletes performed in random order two IT sessions. The two IT comprised 30-s work intervals at either 100% (IT100%) or 105% (IT105%) of vVO2max with 30-s recovery intervals at 50% of vVO2max between each repeat. The parameters of the VO2 kinetics (td1, t1, A1, td2, t2, A2, i.e. time delay, time constant and amplitude of the primary phase and slow component, respectively) during the T lim test were modelled with two exponential functions. The highest VO2 reached was significantly lower (P<0.01) in IT100% run at 19.8 (0.9) km.h-1 [66.2 (4.6) ml.min-1.kg-1] than in IT105% run at 20.8 (1.0) km.h-1 [71.1 (4.9) ml.min-1.kg-1] or in the incremental test [71.2 (4.2) ml.min-1.kg-1]. The time sustained above 90% of VO2max in IT105% [338 (149) s] was significantly higher (P<0.05) than in IT100% [168 (131) s]. The average T lim was 244 (39) s, t1 was 15.8 (5.9) s and td2 was 96 (13) s. t1 was correlated with the difference in time spent above 90% of VO2max (r=0.91; P<0.01) between IT105% and IT100%. In conclusion, athletes with a slower VO2 kinetics in a vVO2max constant-velocity test benefited more from the 5% rise of IT work intensity, exercising for longer above 90% of VO2max when the IT intensity was increased from 100 to 105% of vVO2max.